Efficacy of Vedolizumab in a Nationwide Cohort of Elderly Inflammatory Bowel Disease Patients. Issue 5 (10th July 2021) - Khan, Nabeel; Pernes, Tyler; Weiss, Alexandra; Trivedi, Chinmay; Patel, Manthankumar; Medvedeva, Elina; Xie, Dawei; Yang, Yu-Xiao
Abstract: Background: The elderly inflammatory bowel disease (IBD) population has historically been under-represented in clinical trials, and data on the efficacy of biologic medications in elderly IBD patients are generally lacking. Our study aims to evaluate the efficacy of vedolizumab (VDZ) among elderly IBD patients and compare it with younger IBD patients in a nationwide population-based cohort of IBD patients. Methods: We conducted a retrospective cohort study of patients within the US national Veterans Affairs Healthcare System (VAHS). Patients were stratified into 2 groups based on age at the time of starting VDZ (60 years of age and older or younger than 60 years of age) with outcomes compared between the 2 groups. The primary outcome was steroid-free remission during the 6- to 12-month period after starting VDZ therapy among those patients who were on steroids when VDZ was started. Results: There were 568 patients treated with VDZ, of whom 56.7% had Crohn's disease and 43.3% had ulcerative colitis. Among them, 316 patients were on steroids when VDZ was started. The percentage of patients who were on VDZ and off steroids during the 6- to 12-month period after VDZ initiation was 46.8% and 40.1% for the younger and elderly groups, respectively ( P  = 0.2374). Rates of hospitalization for an IBD-related reason within 1 year of VDZ start among the whole cohort were nearly identical in the younger and elderly groups (11.2% vs 11.3%, P  = 0.9737). Rates of surgery for an IBD-related reason within 1 year of VDZ start were also similar between the young and elderly (3.9% vs 3.9%, P  = 0.9851). Conclusions: In a nationwide real-world retrospective cohort study of elderly IBD patients, we found that the efficacy of VDZ was similar among younger and older IBD patients and comparable with the published data in clinical trials.